Pengaruh Reward, Punishment, dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan di PT XYZ - Annisa Suci Wulandari; Achmad Fauzi; Dian Sudiantini (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research is used to measure the effect of reward, punishment, work environment on job satisfaction of PT XYZ employees. This research uses quantitative research with a quantitative cross-sectional approach. The object used in this study is the employees of PT XYZ with a population of 280 employees. The sample used in this study used purposive sampling technique with the number of samples used in this study as many as 74 respondents determined by the Slovin formula. The analysis method uses the SmartPLS 4.1.0.3 analysis tool, namely the outer model test, inner model test, and hypothesis testing. The results of this study explain that 1) the reward variable has a positive and significant effect on employee job satisfaction; 2) the punishment variable hasn’t significant effect on employee job satisfaction; and 3) the work environment variable has a positive and significant effect on employee job satisfaction.